Functions of professional and value orientations - Murzina, O. A.; Kozhan, O.; Anwaruzzaman Moriam; Мурзіна, Олена Анатоліївна; Кожан, Олена Євгеніївна (My University, 2021)
The article considers the functions that perform professional value orientations in the psychological system of the individual. Through the functions the essence, the fundamental difference of one phenomenon from another, its differential features are revealed. In the research, on the basis of the analysis of theoretical sources as the basic functions of professional and value orientations necessary for formation of the expert were allocated: normative, regulatory, professional activity and communicative functions. Each of them occupies a special place in the process of vocational education.
Keywords: functions; value; value orientations; professional-value orientations; normative function; regulatory function; communicative function; professional-activity function